Penelitian Tindakan Kelas (PTK) - Muhammad Azis; M. Ridwan Tikollah; Sahade Sahade; Fajriani Azis; Samsinar Samsinar (Institut Nalanda, 2023)
Classroom Action Research (CAR) is research by taking action by the teacher in his own class. This activity is carried out through self-reflection with the aim of improving performance as a teacher. This community service activity was carried out with Community Partnership Program (PKM) Partners at SMK Negeri 7 Pangkep. The problem faced by teachers at SMK Negeri 7 Pangkep is that they do not study learning problems that occur in class and teachers are not used to studying learning problems in class in the form of classroom action research. The method used is interactive lectures and discussions. The results achieved are that teachers can examine learning problems that occur in class and teachers can overcome learning problems in the form of classroom action research.